Makrofungi Diversity In The Sesaot Aik Nyet Forest Area, Buwun True Village, West Lombok, West Nusa Tenggara - Liza Fitriani; Cantika Agustina; Huru’in; Erlin Apriani; Firman Ali Rahman; Meilinda Pahriana Sulastri; Mai Rizali (Yayasan Tajuk Indonesia, 2024)
This research aims to map and identify the types of macrofungi that exist in the Sesaot forest, understand the ecological role played by macrofungi in maintaining the balance of the forest ecosystem, and provide recommendations on sustainable forest management practices. The activity method can be referred to as